Analisis Dampak Banjir Terhadap Ketahanan Pangan di Kalimantan Selatan - Ekawati Laily Ramadhani; Ichwan Setiawan (Jurnal Teknologi Berkelanjutan, 2022)
Indonesia is an agricultural country with a high level of food needs, according to the population in each region. The main food commodity of the Indonesian population is rice. South Kalimantan is the 12th highest rice-producing area in Indonesia and the highest in Kalimantan Island based on data from the Statistics Indonesia in 2019, with a production amount of 1,342,861.82 tons. This makes South Kalimantan a potential rice barn, especially on the Kalimantan Island. However, the frequent flooding in the last few years has caused a lot of agricultural land to be inundated, damaging rice crops and causing rice harvest failure. This study reviews the impact of floods due to annual rainfall on paddy fields in South Kalimantan from 2012 to 2021. A set of historical data of rice production, flood events and annual rainfall were collected from government institution. The research method was analized by quantitatively using statistical analysis and GIS to identify potential affected areas. The results of this study there was a very high correlation between annual rainfall and an increase of floods event (r=0.7286), while between the floods event and rice production in South Kalimantan had a quite strong correlation (r=0.5837). The areas that have a significant reduction of rice production in the last 10 years were Kabupaten Barito Kuala (-541,752.74 tons) and Kabupaten Tapin (-509,033.40 tons).